A Comparative Study Between Standard Monopolar Versus Bipolar Saline Turp: Our Experience in Armed Forces Hospital - Islam, MS; Waheed, SM; Rakib, MA; Chowdhury, A; Amin, MN (Bangladesh Journal of Urology, 2020)
Objective: To-evaluate the outcome of bipolar Versus conventional monopolar transurethral resection of the prostate (TURP) on urinary function. Material and Methods: A total of 300 patients with benign prostatic hyperplasia (BPH) were randomized to bipolar or monopolar conventional TURP treatment groups. Operative and early postoperative variables and complications were recorded and all patients were re-evaluated at 1, 3, 6 and 12 months after surgery using the International Prostate Symptom Score (IPSS), uroflowmetry, post-void residual urine volume (PVR). Results: The operating time was shorter in the monopolar TURP group. Postoperative bleeding and blood transfusion requirements did not significantly differ between the two groups. Sodium levels were significantly lower in the monopolar group than in the bipolar group. Transuretheral resection syndrome developed in two (1.4%) patients in the monopolar group. Both groups had similar and significantly improved IPSS values, maximum urinary flow rate values and PVRmeasurement. Conclusion: Bipolar TURP is a safe and effective procedure that is associated with a relatively longer operating time, a smaller reduction in serum sodium levels and a similar efficacy compared with conventional monopolar TURP. Bangladesh Journal of Urology, Vol. 21, No. 2, July 2018 p 66-70